A randomized controlled trial of a new technique for laparoscopic management of ovarian endometriosis preventing recurrence and keeping ovarian reserve - Mohamed F. Shaltout; Ahmad elsheikhah; Ahmed M. Maged; Moutaz M. Elsherbini; Sherif S. Zaki; Sherif Dahab; Rasha O. Elkomy (BMC, 2019)
Abstract Introduction Laparoscopic cystectomy provides more favourable outcomes as regards the recurrence and subsequent clinical pregnancy rates. It is associated with significant reduction in the ovarian reserve due to the inevitable removal of unaffected ovarian tissue. The aim of our study was to evaluate the efficiency of Surgicel in preventing recurrence of endometriomas after their laparoscopic conservative management (cystectomy or drainage). Material and methods A randomized controlled trial included two hundred women (candidate for conservative laparoscopic management of ovarian endometriomas). They were randomized into four groups; group D in which patients underwent laparoscopic drainage of the endometrioma, group C in which patients underwent laparoscopic cystectomy of the endometrioma, group DS in which patients underwent laparoscopic drainage followed by insertion of Surgicel inside the cyst cavity & group CS in which patients underwent laparoscopic cystectomy of the endometrioma followed by insertion of Surgicel inside the remaining ovarian tissues. All patients were followed up for 2 years & the primary outcome was the recurrence of endometriomas in the ipsilateral ovary & the postoperative ovarian reserve was reassessed as a secondary outcome. Results The Surgicel-treated groups had significantly lower hazard of recurrence compared to untreated groups (p = 0.004). Group CS had significantly lower hazard of recurrence compared to Group D & C (p = 0.014, 0.046 respectively). Group DS had significantly lower hazard of recurrence compared to Group D (p = 0.039) but it not significantly different from Group C (p = 0.112). Group DS had the lowest drop of AMH and was significantly lower than the other three groups. Conclusion Surgicel reduces effectively the recurrence risk of endometriomas and its use during laparoscopic drainage is an effective alternative for traditional laparoscopic cystectomy with minimal affection of the patient ovarian reserve. Trial registration Name of the registry: clinicaltrials.gov. Trial registration number NCT02947724. Date of registration October 28, 2016.